2020
DOI: 10.1007/s13314-020-00402-y
|View full text |Cite
|
Sign up to set email alerts
|

First report of Athelia rolfsii causing stem rot disease on Vasaka (Justicia adhatoda)

Abstract: Athelia rolfsii is a facultative plant pathogen which develops characteristic white mycelial mats and sclerotia at the crown infection sites when conditions are favourable. In July 2019, stem rot symptoms such as dark brown necrotic lesions were observed at collar of the stem base. The infected plants showed dark brown symptoms which later turned into light white mycelial growth with immature white sclerotia, while the isolated fungus was initially white in colour and later turned black. The identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
1
1
0
1
Order By: Relevance
“…The study has shown that vine rot and wilt disease of Telfairia occidentalis that is prevailing in the study area is caused by Athelia rolfsii. The rate of incidence was significantly higher and symptoms of infection were similar to the reports of Mahadevakumar et al, [20] on Cucurbita maxima, [21] on Phaseolus vulgaris, [22] on Justicia adhatoda and [9] on field grown tomato in Northern Nigeria. On other economic crops such as cowpea and peanut, Athelial rolfsii disease has been reported and yield loss attributed to it reaches 50 and 80 % respectively [23,24] [25] and recent studies by Negesa et al, [26,27] in different regions in Africa, where incidence and severity level of blight disease caused by A. rolfsii on field grown tomato reaches 40 -98 %.…”
Section: Discussionsupporting
confidence: 85%
“…The study has shown that vine rot and wilt disease of Telfairia occidentalis that is prevailing in the study area is caused by Athelia rolfsii. The rate of incidence was significantly higher and symptoms of infection were similar to the reports of Mahadevakumar et al, [20] on Cucurbita maxima, [21] on Phaseolus vulgaris, [22] on Justicia adhatoda and [9] on field grown tomato in Northern Nigeria. On other economic crops such as cowpea and peanut, Athelial rolfsii disease has been reported and yield loss attributed to it reaches 50 and 80 % respectively [23,24] [25] and recent studies by Negesa et al, [26,27] in different regions in Africa, where incidence and severity level of blight disease caused by A. rolfsii on field grown tomato reaches 40 -98 %.…”
Section: Discussionsupporting
confidence: 85%
“…and Talaromyces pinophilus (Table 3). No DNA from A. rolfsii was sequenced, since its morphological characteristics were enough to identify it, and they coincided with those described by Kamil et al (2020)…”
Section: Colletotrichum Gloeoesporioidesmentioning
confidence: 63%
“…y Talaromyces pinophilus (Cuadro 3). No se realizó secuenciación del ADN proveniente de A. rolfsii, porque las características morfológicas se consideraron suficientes para su identificación, y coincidieron con las descritas por Kamil et al (2020), micelio blanco algodonoso con presencia de fíbulas, tanto en planta como en medio de cultivo PDA y, el desarrollo de esclerocios esféricos de Cuadro 3. Identificación molecular, porcentaje de similitud, accesión y longitud de la secuencia de ITS de morfotipos recuperados a partir de plantas de frijol común (Phaseolus vulgaris) con y sin síntomas de marchitez, según región productora y variedad.…”
Section: Colletotrichum Gloeoesporioidesunclassified